2022
DOI: 10.3748/wjg.v28.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in traction methods for endoscopic submucosal dissection: What is the best traction method and traction direction?

Abstract: Endoscopic submucosal dissection (ESD) has been developed as a treatment for superficial gastrointestinal neoplasms, which can achieve en bloc resection regardless of the lesion size. However, ESD is technically difficult because endoscopists cannot bring their hand into the gastrointestinal tract, unlike surgeons in regular surgery. It is difficult to obtain sufficient tension in the dissection plane and a good field of vision. Therefore, ESD is associated with a long procedure time and a high risk of adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 84 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…Although many traction strategies are used to assist endoscopic resection of submucosal tumors, these methods are mainly applied passively to provide traction from a certain direction or at a certain stage during the procedure 4 5 . Here, we adopted the active traction method with a snare being anchored to the tumor before the first incision.…”
Section: Figmentioning
confidence: 99%
“…Although many traction strategies are used to assist endoscopic resection of submucosal tumors, these methods are mainly applied passively to provide traction from a certain direction or at a certain stage during the procedure 4 5 . Here, we adopted the active traction method with a snare being anchored to the tumor before the first incision.…”
Section: Figmentioning
confidence: 99%
“…It has been reported that traction-assisted methods provide endoscopists with a better field of view of the submucosa, shortening the ESD duration and reducing its adverse events rate [ 5 ]. Therefore, various ESD traction methods continued to emerge in recent years [ 6 ], all showing advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that traction-assisted methods provide endoscopists with a better eld of view of the submucosa, shortening the ESD duration and reducing its adverse events rate. 5 Therefore, various ESD traction methods continued to emerge in recent years, 6 all showing advantages and disadvantages. Our previous report showed that the combined orthodontic rubber band (ORB) and clip traction-assisted ESD achieved good results in colorectal tumors.…”
Section: Introductionmentioning
confidence: 99%